A Prenylated Flavanone from Dalea elegans Inhibits Rhodamine 6 G Efflux and Reverses Fluconazole-Resistance in Candida albicans - Peralta, Mariana A.; Calise, Maximiliano; Fornari, M. Cecilia; Ortega, M. Gabriela; Diez, Roberto A.; Cabrera, José L.; Pérez, Cristina (Planta Medica, 2012)
In previous studies, 2′,4′-dihydroxy-5′-(1′′′,1′′′-dimethylallyl)-6-prenylpinocembrin, a prenylated flavonoid isolated from Dalea elegans roots, showed activity against multiresistant Staphylococcus aureus and Candida albicans, as well as an uncoupling effect on mitochondria and antioxidant activity. The aim of this study was to evaluate the inhibitory effects of 2′,4′-dihydroxy-5′-(1′′′,1′′′-dimethylallyl)-6-prenylpinocembrin and fluconazole on the efflux of rhodamine 6 G in azole-resistant C. albicans 12–99 that expresses multidrug transporters Cdr1p, Cdr2p, and Mdr1p. The effect of fluconazole and 2′,4′-dihydroxy-5′-(1′′′,1′′′-dimethylallyl)-6-prenylpinocembrin on rhodamine 6 G efflux was assessed in both azole-sensitive and azole-resistant C. albicans. Between 1 and 1000 µM, 2′,4′-dihydroxy-5′-(1′′′,1′′′-dimethylallyl)-6-prenylpinocembrin inhibited rhodamine 6 G efflux only in azole-resistant C. albicans 12–99 in a concentration-dependent manner (IC50 = 119 µM); a competitive effect was observed. It also showed selectivity of action in comparison with other flavanones (6-prenylpinocembrin, isolated from aerial parts of D. elegans, pinocembrin, naringenin, and hesperetin, all at 250 µM). To check the possible implications of the inhibition of azole efflux on cell growth, antifungal assays were conducted. Minimal inhibitory concentration values were 150 µM for 2′,4′-dihydroxy-5′-(1′′′,1′′′-dimethylallyl)-6-prenylpinocembrin and higher than 400 µM for fluconazole. The combination of both compounds at either inhibitory or subinhibitory concentrations was significantly more effective than each compound separately. Minimal inhibitory concentration for fluconazole decreased by more than 400 times in the presence of 100 µM 2′,4′-dihydroxy-5′-(1′′′,1′′′-dimethylallyl)-6-prenylpinocembrin, reversing azole resistance and giving values similar to those of azole-sensitive C. albicans. These data are consistent with a dual action of 2′,4′-dihydroxy-5′-(1′′′,1′′′-dimethylallyl)-6-prenylpinocembrin: direct antifungal effect on azole-resistant C. albicans 12–99 and inhibition of azole transporters, which results in reversion of fluconazole resistance.
Keywords: prenylated flavonoid; Dalea elegans; Fabaceae; rhodamine efflux inhibition; antifungal activity; azole-resistant Candida albicans; reversion of fluconazole resistance